Disappearance of women and girls in Mexico: Contributions of feminisms for understanding macrosocial processes - María de Lourdes Velasco-Domínguez; Salomé Castañeda-Xochitl (Íconos, 2020)
According to the 2019 information from the National Registry of People Missing or Disappeared, beginning in 2007 the number of disappearances in the country has increased with more men missing than women. However, the opposite tendency is true with minors because more girls than boys have gone missing. This article proposes some hypotheses to understand this increase in girls who have disappeared in Mexico. A discussion of feminist theories, which seek to understand the increased violence towards young women in the context of neoliberal policies, is presented. This re-search argues that the increase in disappeared girls is associated with two main factors: an economy of dispossession of human lives for the accumulation of capital, which produces specific forms of violence against women and girls, and a systematic violence against women exercised by agents from state security and legal institutions.